Compulsory acquisition of minority shareholding : a critical analysis - Smit, Albertus Ebenhaezer (Department of Commercial Law, 2016)
The compulsory acquisition refers to situations where the minority shareholders are compelled to dispose of their shares. In certain instances the minority shareholders can compel the majority to acquire their shares by an enforced acquisition. The compulsory aspect is thus the unilateral and coercive aspect of the transaction that can arise subject to the fulfilment of certain statutory and regulatory requirements. These transactions are commonly known as squeeze-outs or freeze-outs, whereas sell outs is where minority shareholders have the right to have their shares acquired by the company on a compulsory basis. In this dissertation the argument will be made that the objective of these forms of transactions is to relieve the majority or controlling shareholder from undue oppression by the minority shareholders not only in instances of control transferred squeeze outs but also in respect to control maintained transactions. The dissertation will focus on the three main forms of squeeze-out transactions being the tender offer squeeze-out, the squeeze-out by means of a fundamental transaction and the supermajority squeeze-out transaction. The emphasis will be on how the first two forms of transactions are implemented in the South African context and a case will be made to include the final form in t out legal framework. A specific emphasis will be given to the regulation of these transactions in ensuing the fairness to the affected minority shareholders.